The China Threat Narrative in American Bestselling Non-Fiction Books - Lähteenmäki, Emma (My University, 2026)
In this thesis, I examine contemporary perceptions of the China threat in the United States by analyzing American bestselling, non-fiction literature. The purpose of the research is to investigate how China, and the perceived China threat, are portrayed and constructed. Additionally, I observe what types of policy recommendations the authors of the bestselling books propose for the American leadership to confront the challenge of a rising China. The data of the research consists of ten bestselling China threat books, released during the first term of Donald Trump (2017–2021) and the subsequent Joe Biden presidency (2021–2025). The books were selected from the Amazon.com ‘Bestsellers in Asian Politics’ -list. The research deploys thematic narrative analysis to trace patterns and identify reoccurring tropes in the China threat literature. The findings of the primary source analysis are interpreted by adopting Chengxin Pan’s China threat discourse -dichotomy and Weiqing Song’s three modes of securitizing the China threat. The results of this research posit that the contemporary China threat literature reproduces popular threat tropes that have already been identified by previous research on the topic. These are: China as a military, ideological, political and economic threat. An additional threat category, representing China as a threat to the international system, was also identified. The study finds that the authors of the bestselling, China threat books propose containment and competition-oriented policy approaches for the US in order to respond to the challenges posed by a rising China. The primary source analysis further indicates that the authors mostly agree on the types of behavior that are interpreted as threatening towards the US. However, the authors’ assessments on China’s intentions differed considerably. Moreover, the research shows that the ten bestsellers belonging to the ‘China threat’ genre can be further categorized into two separate subgenres including popular books and expert manuals. Alternatively, Weiqing Song’s three modes of securitization can be used to interpret the books’ intentions and categorize them into distinct modes. Finally, the study extends some critique onto the China threat bestsellers for their biased representation and disregard for American strategies which have historically resembled those adopted by China today. The research concludes that the contemporary China threat literature is part of a historical continuum of Western and American representations of China. This representation has traditionally served the political interests of the West or the US and it contemporarily functions as a legitimizer of the American hegemonic position.
Keywords: China, distribution of power, hegemony, international relations, the People’s Republic of China, narratives, othering, representation, securitization, Sino-US relations, the United States, the China threat